Par temps agités - Antoine Faure (Temporalités)
Do order and crisis alternate in journalistic temporalities? The case of Popular Unity in Chile (1970-1973) shows that practical routines and discursive habits in journalism are historically situated and can metamorphose. The transformations are backed by established norms but cause other temporal logics to emerge, which slowly get the upper hand. In Chile, the temporality of agenda-setting and the figure of gatekeeper are challenged by political events and media urgency. The selection and newsworthiness of information don’t disappear, but their objectives change. They leave room for fluidity in a temporality that journalists use to provide an extended and accelerated flow of information. Reactivity is redefined. Popular Unity therefore implies those turbulent times in Chile when the temporality of agenda-setting changed. It is important to study this case because of the historical differences between the changes that took place in journalism and the succession of political regimes, since the temporality of fluidity emerged during Salvador Allende’s democratic government and was consolidated under the authoritarian regime of Pinochet.